Evaluation of sooting tendency of acetone–butanol–ethanol (ABE) fuels blended with diesel fuel. (1st December 2017) - Luo, Jianfei; Zhang, Yongming; Zhang, Qixing; Liu, Jia; Wang, Jinjun
Highlights: ABE-diesel has a lower sooting tendency compared with butanol-diesel. Sooting tendency can be ordered as follows: acetone-diesel > butanol-diesel > ethanol–diesel. Ethanol and butanol enhance the ability of ABE to reduce sooting tendency. The extra acetone weakens the ability of ABE to reduce sooting tendency. Abstract: Acetone–Butanol–Ethanol (ABE), the intermediate product in bio-butanol production process using Biological Fermentation Purification technology, has been proposed to blend diesel directly for saving the high energy requirement of separating purity butanol. It is very important to study the sooting tendency of ABE-diesel blends, which determined whether it can be used as a clean alternative fuel. Therefore, in this paper, the smoke point and relationship between flame height and fuel uptake rate for a wide range ratio of ABE (0%, 5%, 10%, 20%, 30%, 50% in volume referred to as D100, ABE5, ABE10, ABE20, ABE30, and ABE50, respectively) were measured using wick-fed burner. Flame heights were captured by a Digital SLR camera and fuel uptake rate were gained from electronic analytical balance. It was observed that flame height versus fuel uptake rate started with a linear relationship, then disjointed points appeared, finally returned linear again. Threshold Sooting Index (TSI) and Oxygen Extended Sooting Index (OESI) calculated from fuel uptake rate and smoke point respectively were used to evaluate the blends' sooting tendency. ABE-diesel has a lower sooting tendency than butanol-diesel because it owns higher oxygen content and lower carbon content for the same blend ratio. Besides, the contribution of acetone, butanol and ethanol to the intensity of ABE weaken blends' sooting tendency were tested through increasing their relative concentrations in ABE. Since ethanol and butanol have higher H/C ratio and oxygen content from the view of molecular structure, their content in ABE play a positive role in weakening sooting tendency, while the acetone content in ABE has an opposite effect because of its unsaturation degree.